Determining Jurisdiction and the Applicable Law in Cross-Border Unfair Competition and Unfair Commercial Practices Cases - Rohová, Iveta; Sehnálek, David (LeXonomica, 2017)
The free movement of goods promotes cross-border transactions. Computerization of services and intensified use of the Internet also contribute to the development of trade within the EU. Problems that could once be addressed almost exclusively or at least prevailingly at a national level currently assume cross-border character. This is also true in the case of regulation of unfair competition and unfair commercial practices. Whereas the substantive regulation of unfair competition in both EU and domestic law is quite common in scientific literature, its aspects in private international law are often neglected. Since the EU law has to a large extent replaced national conflict-of-law and procedural rules with unified EU provisions, this article focuses on the EU regulations Rome II and Brussels I bis with the emphasis put on the latter. The aim of this article is to review the rules determining jurisdiction (and the applicable law) on the basis of legal doctrine, current legislation and case law of the Court of Justice of the EU. Attention also will be paid to both off-line and on-line situations, as well as to the specifics of consumer protection in the context of unfair competition and unfair commercial practices.